Early life lead exposure as a risk factor for aggressive and violent behaviours in young adults: A retrospective systematic review - Obamuyide, Henry (Department of Public Health and Family Medicine, 2021)
Over 1.3 million individuals die each year from preventable violence. Many of these violent acts are perpetrated by youths. Despite several initiatives, the prevalence of youth violence remains high. Early life lead exposure is a possible cause of aggressive and violent behaviour in young adults. Several aggregate-level and individual-level studies report an increase in risk of violent behaviour with increasing lead exposure. However, the evidence base for the role of lead in violence is conflicting as many other studies did not support this claim. No systematic synthesis of current evidence at the individual level exists to critically assess this association. Therefore, we planned to conduct a systematic review and meta-analysis of studies examining the relationship between lead exposure in early life and the later development of aggressive and violent behaviour in young adulthood at the individual level. Extensive literature searches, including of grey literature, were performed to identify potentially relevant articles. Studies for inclusion were screened by two reviewers and selected using pilot-tested eligibility form. The two reviewers independently assessed risk of bias and carried out data extraction before analysis. A systematic review and meta-analysis of currently available evidence was carried out. Searches were conducted between September 2019 and October 2019. We identified a total of 2182 reports, out of which six studies in 7 publications were eligible. All of the studies were conducted in high income countries, though a few recruited participants from low-income communities. There were varying definitions of violence, ranging from very narrow to wide and the outcomes were measured as either a count or binary variable. Despite the diversity in study settings, the direction of findings was remarkably homogenous. For studies reporting dichotomous variable, the odds of being arrested or convicted for violent behaviour increases with increasing blood lead level (OR 1.13 to 1.16 with each 5µg/dl rise in blood lead) after controlling for other variables. For the studies reporting count outcome, blood lead may explain up to 63% of the variability in arrest or conviction rates after adjusting for co-variates (IRR for each 5µg/dl rise in blood lead level:1.1 to 1.13). Overall, using a random-effect model with restricted maximum likelihood estimation method, blood lead was associated with a higher risk of exhibiting violent behaviour (OR 1.16; 95% CI 1.10 – 1.23). There was insufficient data to perform sensitivity analyses based on study design, quality of studies or conduct a dose response meta-analysis. We found that an increased exposure to lead in childhood is associated with a higher risk of being arrested or convicted for violent behaviour in young adulthood. In this context, environmental lead control may help to reduce the prevalence of aggressive and violent behaviour in young adults and should be integrated into violence prevention strategies. Despite the ubiquity of environmental lead, the importance of violence as a public health and social concern and the considerable debate their association has generated, we found very few good quality studies that reported enough methodological detail for evidence synthesis. More studies with better quality and from different settings need to be conducted.